V band photometry of the SN 2003GF supernova utilizing the 2mass catalog - Reyes, RC (2013)
This research was carried out as part of the project titled "Variabilidad Estelar en la Galaxia" (Stellar Variability in the Galaxy) supported by CONCYTEC (Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica, Peru). We also thank the 2MASS, SIMBAD, ALADIN, and VSNET online databases which allowed us access to valuable data from other observers.